2017
DOI: 10.1111/1348-0421.12536
|View full text |Cite
|
Sign up to set email alerts
|

Indices of anti‐dengue immunoglobulin G subclasses in adult Mexican patients with febrile and hemorrhagic dengue in the acute phase

Abstract: Heterologous secondary infections are at increased risk of developing dengue hemorrhagic fever (DHF) because of antibody-dependent enhancement (ADE). IgG subclasses can fix and activate complement and bind to Fcɣ receptors. These factors may also play an important role in the development of ADE and thus in the pathogenesis of DHF. The aim of this study was to analyze the indices of anti-dengue IgG subclasses in adult patients with febrile and hemorrhagic dengue in the acute phase. In 2013, 129 patients with de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Thein et al 22 showed that serum from subjects with acute DHF or DSS contained higher levels of anti-DENV IgG1 subclass of IgG. Likewise, Posadas-Mondragon et al 23 reported that IgG1 subclass of DENV specific IgG was the predominant subclass during both primary and secondary DENV infections that significantly increased in the patients with secondary DENV infection and DHF. Others 24 have shown that high levels of DENV specific IgA, IgG1, and IgG4 antibodies in serum were markers of high risk for DSS and DHF.…”
Section: Discussionmentioning
confidence: 98%
“…Thein et al 22 showed that serum from subjects with acute DHF or DSS contained higher levels of anti-DENV IgG1 subclass of IgG. Likewise, Posadas-Mondragon et al 23 reported that IgG1 subclass of DENV specific IgG was the predominant subclass during both primary and secondary DENV infections that significantly increased in the patients with secondary DENV infection and DHF. Others 24 have shown that high levels of DENV specific IgA, IgG1, and IgG4 antibodies in serum were markers of high risk for DSS and DHF.…”
Section: Discussionmentioning
confidence: 98%
“…IgG3 is often one of the earliest subclasses to be elicited against protein antigens upon infection [3,[61][62][63], due to its genetic locus positioning among Ig heavy constant chains (IGHC) in humans [64,65]. Sequentially, IgG3 is the first IGHG gene located within the locus, followed by IgG1 (Gene order as follows: IGHG3, IGHG1, IGHA1, IGHG2, IGHG4, IGHE, and IGHA2 from 5' to 3' [64,65]); thus IgG3 responses are often closely followed by IgG1 responses.…”
Section: Generation Of Igg3 During Various Infection Typesmentioning
confidence: 99%
“…One study found that Chikungunya virus-specific responses are dominated by neutralizing IgG3 Abs, which developed rapidly in patients with high viremia [75]. In contrast, pre-existing IgG in patients, mainly IgG1 and IgG3, against severe Dengue virus (DENV) can form virus-Ab complexes with a different DENV serotype, promoting infection which can lead to complications, such as dengue hemorrhagic fever and dengue shock syndrome [62,76,77]. This cross-serotype activity is referred to as Ab-dependent enhancement (ADE), that is theorized to be due to higher antigen avidity [34], activation of complement [62], and FcγR binding [78,79] compared to same serotype responses.…”
Section: During Early Hiv Infection Functional Ab Responses Decline Drastically With Hivmentioning
confidence: 99%
“…Using published criteria for clinical assessment (Tomashek et al 2018), 27.7% of our patients with PI qualified as severe thrombocytopenia and 38.8% had moderate thrombocytopenia, without significant differences compared with SI (Table 4). We observed a decrease in albumin, along with elevated alanine transaminase (ALT) and aspartate transaminase (AST) in both PI and SI (Table 4) denoting liver inflammation, which has been associated with severity (Oliveira et al 2016, Posadas-Mondragón et al 2017; however, there were no cases of acute hepatitis marked by >10 times ALT increase, unlike in other studies (Souza et al 2004). It has been reported that Ca 2+ levels correlate with disease severity, with hypocalcemia being more prevalent in DHF than in DF (Constantine et al 2014).…”
Section: Discussionmentioning
confidence: 63%